2021
DOI: 10.1371/journal.pone.0250294
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate preparedness for response to COVID-19 is associated with stress and burnout among healthcare workers in Ghana

Abstract: Introduction The COVID-19 pandemic has compounded the global crisis of stress and burnout among healthcare workers. But few studies have empirically examined the factors driving these outcomes in Africa. Our study examined associations between perceived preparedness to respond to the COVID-19 pandemic and healthcare worker stress and burnout and identified potential mediating factors among healthcare workers in Ghana. Methods Healthcare workers in Ghana completed a cross-sectional self-administered online su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
129
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(148 citation statements)
references
References 42 publications
15
129
2
2
Order By: Relevance
“…One potential unexplored predictor is providers' perceived preparedness to respond to the pandemic. In a prior study in Ghana, we found that HCWs did not feel prepared for the pandemic response [33], contributing to high stress and burnout [34], which has implications for job satisfaction.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…One potential unexplored predictor is providers' perceived preparedness to respond to the pandemic. In a prior study in Ghana, we found that HCWs did not feel prepared for the pandemic response [33], contributing to high stress and burnout [34], which has implications for job satisfaction.…”
Section: Introductionmentioning
confidence: 84%
“…The14-item Shirom-Melamed Burnout measure (SMBM) captured feelings at work in the past month [49], across three-domains of burnout: physical fatigue, emotional exhaustion, and cognitive weariness and with response options ranging from 1 (never or almost never) to 7 (always or almost always). Additional methods have also been previously described [34]. The psychometric properties for both measures have been previously assessed in SSA [34,50].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghana recorded a mild type of COVID-19 infection, with minimal secondary infection rate and lower-case fatality rate in addition to a drastic reduction in new COVID-19 cases as compared to the early stages of the outbreak [ 2 ]. Also, there is an increasing awareness and knowledge of COVID-19 transmissions, risk factors, and effectiveness of safety protocol [ 23 24 25 26 ]. Therefore, ones' perception or fear of contracting the virus could be relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…There is still a lack of information that would help health care managers and policymakers in the era of COVID-19 to improve the delivery of health care quality and to learn for the future [5]. Higher pandemic burdens such as HCWs' burnout and stress are expected when the Health Care Organizations (HCOs) lack plans and preparedness to strengthen their surge capacity and HCWs' resilience [6,7].…”
Section: Introductionmentioning
confidence: 99%